PENGARUH MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) BERBANTUAN ALAT PERAGA TERHADAP HASIL BELAJAR PADA MATERI GAYA PEGAS - Mirna Hoke; Ferdy Dungus; Tineke Makahinda (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Physics is one of the subjects taught in Senior High School (SMA) education. Physics learning is often seen as an abstract science that is presented in a theory that is less attractive and seems difficult to master and understand. To solve the problem of learning physics, one of the models that is expected to increase the activeness and learning outcomes of students is to apply the Problem Based Learning (PBL) learning model. The use of variations in the PBL learning model with teaching aids and conducting experiments is also considered to make students not easily bored in learning physics and makes the material tend to be easily understood by students. For this reason, a study was conducted with the aim of knowing the effect of the Problem Based Learning (PBL) learning model assisted by teaching aids on the material of spring force on student learning outcomes. The data analysis technique in this research is using normality test and hypothesis testing. The results of the normality test showed that the data were normally distributed, and the results of the hypothesis test showed that the application of the PBL learning model assisted by teaching aids proved to have an effect on improving student learning outcomes.